Eriophyid mite vector of Rose Rosette Disease (RRD) Phyllocoptes fructiphilus Keifer (Arachnida: Acari: Eriophyidae) - Marjorie Hoy (EDIS, 2013)
Phyllocoptes fructiphilus Keifer, a tiny eriophyid mite, is the vector of a devastating viral disease of roses called Rose Rosette Disease (RRD). This mite can be spread by the wind and by contaminated clothing and equipment. It also is possible that it can disperse through phoresy (attaching itself to insects). As a result, the distribution of the mite and RRD is expanding. This 5-page fact sheet was written by Marjorie Hoy and published by the UF Department of Entomology and Nematology, May 2013.